Dampak ESG, Green Accounting, dan Kepemilikan Institusional terhadap Nilai Perusahaan: Studi Kasus pada Sektor Energi yang Terdaftar di BEI Periode 2021–2023 - Putri, Mia Helmalia; Setiawan, Ricky Yunisar; Wibowo, Agus Satrya (Jurnal KIAFE, 2025)
This study examines the effects of sales growth, Investment Opportunity Set, Working Capital Turnover, and free cash flow on firm value in property and real estate companies listed on the Indonesia Stock Exchange during the 2018–2020 period. The study employs a quantitative associative approach using secondary data obtained from audited financial statements. The sample was selected through purposive sampling and consisted of 46 companies, resulting in 138 initial firm-year observations. After eliminating 39 outlier observations, 99 observations were included in the final analysis. Firm value was measured using Price-to-Book Value, while Investment Opportunity Set was proxied by current assets to net sales. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with IBM SPSS version 25. The results show that Working Capital Turnover and free cash flow have positive and significant effects on firm value. Sales growth has a negative but insignificant effect, while Investment Opportunity Set has a positive but insignificant effect. Simultaneously, the four independent variables do not significantly affect firm value. The adjusted coefficient of determination is 5.4%, indicating that the model has limited explanatory power.